Revolusi Industri 4.0: Googelisasi Industri Pariwisata dan Industri Kreatif - Poerwanto Poerwanto; Yoedo Shambodo (Journal of Tourism and Creativity, 2020)
Today’s technology revolution engages the 4th wave which is called 4.0 industrial revolution. This 4.0 industry refers to technology that produce to digital technology. Entrepreneurship world has experienced a great transformation which has turned from conventional technology into the digital one. Google has created various of apps those are constructing the communicating ecosystem. The google-based technology facilatates the production process. It is really challenges and opportunity for Indonesian tourism industry and creative industry. Keyword: industry 4.0, googlization, tourism industry, creative industry